ChemInform Abstract: Hydrogenation of Allyl Alcohols Catalyzed by Aqueous Palladium and Platinum Nanoparticles. Issue 2 (23rd December 2015) - Di Pietrantonio, Krystel; Coccia, Francesca; Tonucci, Lucia; d'Alessandro, Nicola; Bressan, Mario
Abstract: Six different platinum nanoparticles and six different palladium nanoparticles are prepared and screened as catalysts for the hydrogenation of allylic alcohols.